The big sleep [videorecording (DVD)] - Hawks, Howard, 1896-1977; Bogart, Humphrey, 1899-1957; Bacall, Lauren, 1924-2014; Chandler, Raymond, 1888-1959 (Warner Home Video, 2000)
L.A. private eye Philip Marlowe takes on a blackmail case and follows a trail peopled with murderers, pornographers, nightclub rogues and the spoiled rich.